Sodium hydrogen bicarbonate and water as blowing agent in palm kernel oil based polyol polyurethane foam. (2021) - Fawzi, T.; Yu, L.J.; Badri, K.H.; Sajuri, Zainuddin; Al-Talib, Ammar Abdulaziz Majeed; Noum, Se Yong Eh
Abstract: Palm kernel oil polyol based flexible polyurethane foams were synthesized by using two different types of natural blowing agentswater and sodium hydrogen bicarbonate (SHB), as alternatives to replace the climate change accelerating blowing agents (BA). The samples have been studied and analyzed by scanning electron microscopy (SEM), density measurements, Fourier transform infrared (FT-IR) spectroscopy and tear resistance test. SEM has revealed that adding water (2 php) has increased the cell size by 157% and pore size by 226%, while adding water (2 php) and SHB (25 php) have increased the cell size and pores by 276% and 920%, respectively. The addition of natural BAs has impacted struts differently. SHB has resulted in thicker struts compared to water due to increment of polyurethane mixture's viscosity. FT-IR spectroscopy has confirmed that both BAs did not affect the polyurethane's functionalities, nor did react with any of the reactants. The absence of (–NCO) functionality peaks attributed to full exploitation of diisocyanate during the foaming reaction. It was found that additional of (2 php) water in the PU had reduced the density by 24%. On the other hand, additional of SHB (2 php) into PU, has increased the density of the foam, under water deficiency condition. It has been found that, adding 2 php SHB resulted high tear resistance strength (0.76 N/mm), which has shown an improvement of 26% of tear resistance strength as compared to the sample without blowing agents.